2020
DOI: 10.1037/xge0000679
|View full text |Cite
|
Sign up to set email alerts
|

A model for two-digit number processing based on a joint Garner and system factorial technology analysis.

Abstract: As a vital part of our daily lives, number processing has received much attention in current cognitive research. Most adults perceive with ease the numerical magnitude of a two-digit number and also the individual magnitudes of the component digits, yet the relation between the 2 is poorly understood. Application to two-digit numbers of Garner’s speeded classification paradigm (Experiment 1) and of system factorial technology (Experiment 2) jointly reveals phases of independent and of coactive processing withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 106 publications
0
16
0
Order By: Relevance
“…Strong evidence for the absence of information integration in composite faces comes from application of the redundant target task (Miller, 1982) and the system factorial technology (SFT, Townsend & Nozawa, 1995) to composite faces (Fitousi, 2015; see also Cheng, McCarthy, Wang, Palmeri & Little, 2018). The SFT is a powerful mathematical theory accompanied by a set of methodological tools capable of diagnosing fundamental processing characteristics (Fitousi, 2019a; Fitousi & Algom, 2018, 2019). The SFT affords qualitative and quantitative identification of the underlying processing system (serial, parallel, or coactive).…”
Section: Non-holistic Accounts Of the Composite Face Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong evidence for the absence of information integration in composite faces comes from application of the redundant target task (Miller, 1982) and the system factorial technology (SFT, Townsend & Nozawa, 1995) to composite faces (Fitousi, 2015; see also Cheng, McCarthy, Wang, Palmeri & Little, 2018). The SFT is a powerful mathematical theory accompanied by a set of methodological tools capable of diagnosing fundamental processing characteristics (Fitousi, 2019a; Fitousi & Algom, 2018, 2019). The SFT affords qualitative and quantitative identification of the underlying processing system (serial, parallel, or coactive).…”
Section: Non-holistic Accounts Of the Composite Face Effectmentioning
confidence: 99%
“…These stimuli fuse the top and bottom halves from two different identities to give the impression of a novel face (Young et al, 1987). The illusion is reduced or gone when the face halves are misaligned or inverted (Fitousi, 2016, 2019; Richler, Gauthier, et al, 2008). The illusion has been documented with familiar faces (Young et al, 1987) and unfamiliar faces (Fitousi, 2013, 2015; Hole, 1994; Michel et al, 2006; Richler, Tanaka, et al, 2008) alike.…”
Section: Introductionmentioning
confidence: 99%
“…1 Holistic processing in SFT entails a distinct process model called coactivation (Miller, 1982; Townsend and Nozawa, 1995). In coactive systems information from two facial features or parts should coalesce into a single channel, producing well-known effects of supercapacity and coactivation (Townsend and Nozawa, 1995; Fitousi, 2015; Fitousi and Algom, 2018, 2019) on response latencies distributions (Miller, 1982, 1986; Townsend and Wenger, 2004). When tested against this well-defined model, faces have failed to exhibit expected holistic signatures (Fitousi, 2015; Cheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In all the experiments the sequences presented two digit numbers at a rate of 4/s and sequencelength was randomly selected to be either 6 or 12 items (based on Brezis et al, 2015, we avoided shorter sequence lengths to discourage explicit computation strategies, which were found for sequences of 4 items). Previous research has indicated that the number magnitude is automatically encoded when subjects are presented with two digit numbers (Dehaene et al, 1990;Fitousi and Algom, 2019). In Experiments 1a and 1b, we require participants to evaluate only the sequence average (see Figure 3).…”
Section: Methodsmentioning
confidence: 99%